Chaotic Watermarking for Authentication - Melad Saeed (Al-Rafidain Journal of Computer Sciences and Mathematics)
This research concerns with generating and hiding invisible chaotic watermarking, in a manner different from that used in the rest of the known watermarks, has been presented. The work has two phases in each of which the chaotic function has been used twice. In the first phase it is used to generate the watermark from the same cover picture then embedding it in another level of the cover depending on the chaotic positions in order to increase authenticity and fortification against attacks. As for the second phase, the chaotic function has been used to generate and retrieve the watermark and compare them to ensure authenticity. Through the practical results that were obtained using the measurements of Correlation, PSNR, and MSE the quality of this algorithm has been shown. Some of the image processing procedures have been used to measure the robustness of this algorithm through calculating the correlation coefficient.